Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.2141/jpsa.0170011
|View full text |Cite
|
Sign up to set email alerts
|

Egg Production, Egg Quality, Blood Profiles, Cecal Microflora, and Excreta Noxious Gas Emission in Laying Hens Fed withFenugreek (<i>Trigonella foenum-graecum</i> L.) Seed Extract

Abstract: This study was designed to investigate the effects of dietary fenugreek seed extract (FSE) supplementation on egg production, egg quality, blood profiles, cecal microflora, and excreta noxious gas emission in laying hens. A total of 384 laying hens (26-weeks old, Hyline-brown) were fed three different levels of FSE (0, 0.05, and 0.1%) in a cornsoybean diet for 6 weeks. The inclusion of FSE in the laying hen diet did not affect egg production, feed intake, or feed conversion among treatments; however, egg weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…According to the present study result, the supplementation of MOLM (T2), FSP (T6), and their combination in T3, T4, and T5 improved the eggshell thickness and shell strength of Lohmann Brown layers. The results of the current study were in agreement with that of Park et al [73] who reported that supplementation of fenugreek seed on Hy line-brown laying hens significantly (p<0.05) increased the eggshell breaking strength and eggshell thickness compared with the control group. Similarly, the result of Sharmin et al [69] indicated that the addition of MOLM to the hens' diet for a longer period improves shellbreaking strength.…”
Section: External Eggs Qualitiessupporting
confidence: 93%
“…According to the present study result, the supplementation of MOLM (T2), FSP (T6), and their combination in T3, T4, and T5 improved the eggshell thickness and shell strength of Lohmann Brown layers. The results of the current study were in agreement with that of Park et al [73] who reported that supplementation of fenugreek seed on Hy line-brown laying hens significantly (p<0.05) increased the eggshell breaking strength and eggshell thickness compared with the control group. Similarly, the result of Sharmin et al [69] indicated that the addition of MOLM to the hens' diet for a longer period improves shellbreaking strength.…”
Section: External Eggs Qualitiessupporting
confidence: 93%
“…The effectiveness of phytase in improving the eggshell strength may be associated with the utilization of minerals. The color agent present in the diet could affect yolk color, and the yolk color is directly influenced by pigments in the feed ingredients ( Park et al , 2018 ). The results of this study showed that yolk color was affected by phytase supplementation; similar results were documented by Hassanien and Sanaa (2011) .…”
Section: Resultsmentioning
confidence: 99%
“…Lipids play an essential role in animal growth and are one of the main components of egg yolk in laying hens [50,51]. Lipid metabolism in the body of laying hens is high after the laying starts, in the peak laying period.…”
Section: Discussionmentioning
confidence: 99%